EFEKTIVITAS MODEL PEMBELAJARAN BLENDED LEARNING PADA MASA PANDEMI - Seri Zalukhu; Eni Rombe; David Priyo Susilo (JOURNAL of THEOLOGICAL STUDENTS, 2023)
It has been suggested that the blended learning model in SMK Negeri of the 3 Lahewa is less effective. This is because most students claim the use of the blended learning learning model is less helpful to students in understanding the learning materials. It was to identify the extent of blended learning during the pandemic. The methodology used in this study is a quantitative description. Based on hypothesis testing acquired a level of effectiveness of learning blended learning during the pandemic in SMK Negeri 3 Lahewa the year 2021/2022 fall under the category of 57, 28%.